Impact Of Marketing Events On Customer Satisfaction Mediated By Digital Marketing And Moderate Green Marketing On MSMEs In Banyumas District - Antonius Ary Setyawan; Bobby Wiryawan Saputra (Universitas Tidar, 2024)
With the help of digital marketing and green marketing, the purpose of this study is to investigate the influence that marketing events have on customer satisfaction in micro, small, and medium-sized enterprises (MSMEs) located in the Banyumas Regency. The method of sampling is known as simple random sampling. This is due to the fact that the population is quite huge, which means that the samples are taken depending on the convenience that is discovered. To estimate the appropriate size of the sample for this investigation, the Slovin formula was utilized. (0.1) is the absolute maximum percentage of the sample limit that can still be allowed. The distribution of questionnaires to micro, small, and medium-sized enterprises (MSMEs) in the Banyumas Regency was carried out by sending a link to a Google form. The findings of this study indicate that marketing events have an effect on the level of satisfaction experienced by consumers, that digital marketing acts as a mediator during the interaction between marketing events and consumer satisfaction, and that green marketing acts as a moderator during the relationship between marketing events and consumer satisfaction.